APLASTIC SYNDROME IN A PREGNANT WOMAN ON THE BACKGROUND OF COVID-19: A CLINICAL CASE - Индира Венеровна Сахаутдинова; Ирина Борисовна Фаткуллина; Ирина Робинзоновна Рахматуллина; Игорь Сергеевич Засядкин; Анна Юрьевна Лазарева (Мать и дитя в Кузбассе)
Women during the gestational process have high risks of contracting the new coronavirus infection COVID-19 due to significant immunological changes in the body of the expectant mother. Physiological changes are also known in other systems, for example, respiratory, digestive, urinary and cardiovascular, which suggest vulnerability to the influence of pathological agents and the formation of severe infection, which can lead to an increase in maternal morbidity and mortality.